Neuroleptic malignant syndrome following reintroduction of an antipsychotic after overdose. (3rd August 2018) - Korchia, Théo; Blackman, Graham; Cermolacce, Michel; Richieri, Raphaëlle
Abstract : Neuroleptic malignant syndrome (NMS) is a potentially lethal adverse drug reaction. We report a case of NMS potentially induced by dehydration in a female patient suffering from schizoaffective disorder. We discuss possible aetiologies and triggering factors alongside the existing literature.